Evolution of Morphology, Structure and Emission in Si-rich HfO2:Nd films with Annealing Times. Issue 1 (January 2021) - Rivero, A; Torchynska, T; Vega, L; Casas, J; Khomenkova, L; Gourbilleau, F
Abstract: The impact of the time at high temperature annealing on the morphology, crystal structure and emission in visible spectral range has been studied in Si rich HfO2 :Nd films produced by radio-frequency magnetron sputtering in pure argon plasma. The annealing was carried out at 900 °C for 1, 5, 10, 30 and 60 min in the nitrogen atmosphere. A set of experimental methods have been used, such as: scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) and photoluminescence (PL). In the present work the joint analysis of PL and XRD results permits us to estimate the optimal time parameters of annealing at 900 °C the Si-HfO2 : Nd films for obtaining the bright emission via 4f electronic levels of the Nd ions embedded in the tetragonal HfO2 phase mainly after long annealing (30- 60 min). The film oxidation for annealing times (60 min) stimulated some crystal phase transformation with the start of formation of the tetragonal SiO2 phase, that is accompanied by the defect generation and decreasing the PL intensity. The discussion of PL and XRD results is presented in detail.